2001
DOI: 10.1677/jme.0.0260229
|View full text |Cite
|
Sign up to set email alerts
|

The carboxy-terminal domain of IGF-binding protein-5 inhibits heparin binding to a site in the central domain

Abstract: The IGF-binding protein (IGFBP)-5 protein contains consensus heparin binding motifs in both its carboxy (C)-terminal and central domains, although only the C-terminal site has previously been shown to be functional. We have made two chimeric IGFBP proteins by switching domains between rat IGFBP-5 and -2, named BP552 and BP522 to reflect the domains present, and a truncated rat IGFBP-5 mutant (1-168), named BP550. The ability of these proteins and wild-type (wt) IGFBPs-5 and -2 to bind to either IGFs or heparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…HBD peptide derived from IGFBP-2 did not inhibit angiogenesis indicating that angiogenesis inhibition is specific to the heparin-binding site of IGFBP-5. IGFBP-5 has three putative heparin-binding sites: two overlapping sites in the linker domain ( 132 VKKDRRKKL 140 ) and one in the C-terminal region ( 205 YKRKQCKP 212 ); however, only the C-terminal heparin-binding site is functional15. This might explain why VEGF-A expression and tumor growth were inhibited only in 2774 cells stably expressing the C-terminus of IGFBP-5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBD peptide derived from IGFBP-2 did not inhibit angiogenesis indicating that angiogenesis inhibition is specific to the heparin-binding site of IGFBP-5. IGFBP-5 has three putative heparin-binding sites: two overlapping sites in the linker domain ( 132 VKKDRRKKL 140 ) and one in the C-terminal region ( 205 YKRKQCKP 212 ); however, only the C-terminal heparin-binding site is functional15. This might explain why VEGF-A expression and tumor growth were inhibited only in 2774 cells stably expressing the C-terminus of IGFBP-5.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal domain also has a nuclear localization signal and a heparin-binding site. The L-domain also contains a heparin-binding site, but this site has been reported to be nonfunctional15. The heparin-binding domain consists of the consensus amino acid sequence XBBBXXBX or XBBXBX (B: basic amino acid, X: undefined amino acid).…”
mentioning
confidence: 99%
“…This domain has been shown to interact with extracellular matrix proteins, such as fibronectin, thrombospondin-1, osteopontin and vitronectin (Akkiprik et al, 2008). In addition, IGFBP5 contains a total of three heparin-binding motifs in the C-terminal and L domains (Song et al, 2001). These motifs in IGFBP5 bind to glycosaminoglycans in the extracellular matrix and can be blocked by heparin (Song et al, 2001).…”
Section: Igfbp5 In Osteosarcomamentioning
confidence: 99%
“…In addition, IGFBP5 contains a total of three heparin-binding motifs in the C-terminal and L domains (Song et al, 2001). These motifs in IGFBP5 bind to glycosaminoglycans in the extracellular matrix and can be blocked by heparin (Song et al, 2001). The ability of IGFBP5 to bind to extracellular matrix proteins may modulate cell-cell and cell-matrix interactions.…”
Section: Igfbp5 In Osteosarcomamentioning
confidence: 99%
“…Investigation at the molecular level of the interaction between heparin and IGFBP-5 has identified the region lying between residues 201 and 218 as the major heparin binding domain (Arai et al 1996) and an extensive site-directed mutagenesis study within this region of the protein has indicated the importance of specific basic amino acid residues in binding to heparin (Parker et al 1996). Sequence analysis of IGFBPs has also indicated the presence of an 'S type' heparin binding domain in the central region of some IGFBPs (Hodgkinson et al 1994) and further work from our group has shown that there is also a central heparin binding site in IGFBP-5, involving the amino acids Arg136 and Arg137 (Song et al 2001).…”
Section: Introductionmentioning
confidence: 98%